Diagnostic performance of dynamic electrocardiography in the diagnosis of myocardial ischemic attack in coronary heart disease: a systematic review and meta-analysis - Lv, Wenming (Frontiers in Medicine, 2025)
BackgroundCoronary heart disease (CHD) remains a leading cause of mortality worldwide, highlighting the need for early and accurate diagnosis of myocardial ischemia to improve patient outcomes. Dynamic electrocardiography (ECG) has become a critical diagnostic tool due to its capacity for continuous cardiac electrical activity monitoring. However, existing studies show considerable variation in its diagnostic performance. To establish higher-level evidence, this study systematically evaluates the diagnostic accuracy of dynamic ECG for myocardial ischemic episodes in patients with CHD through a comprehensive systematic review and meta-analysis.MethodsA comprehensive literature search was conducted through May 2025 using PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure, and Wanfang databases. Study quality was assessed using the QUADAS-2 instrument. Diagnostic performance was evaluated using sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR), and the area under the receiver operating characteristic curve (AUC).ResultsThe meta-analysis included 24 studies comprising 3,509 participants. The pooled diagnostic performance of dynamic ECG for myocardial ischemia showed a sensitivity of 0.75 (95% CI: 0.70–0.80), specificity of 0.70 (95% CI: 0.64–0.75), PLR of 2.50 (95% CI: 1.99–3.13), NLR of 0.36 (95% CI: 0.28–0.45), DOR of 6.64 (95% CI: 4.55–9.69), and an AUC of 0.79 (95% CI: 0.75–0.82). Subgroup analyses indicated higher diagnostic accuracy in studies involving confirmed CHD cases and those using coronary angiography as the reference standard.ConclusionDynamic ECG exhibits moderate diagnostic value for detecting myocardial ischemia in patients with CHD. Its clinical application should be integrated with complementary diagnostic approaches. Further high-quality research is necessary to confirm its diagnostic utility and refine implementation protocols.Systematic review registrationINPLASY202560026.